On the formula of generalized resolvents of a non-densely defined Hermitian operator - Malamud , M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The Weyl function and the prohibited lineal, corresponding to a given space of boundary values of a nondensely defined Hermitian operator, are introduced and investigated. The prohibited lineal is characterized in terms of the limiting values of the Weyl function. An analogue of M. G. Krein’s formula for the resolvent is obtained and its connection with the space of boundary values is found.